2018
DOI: 10.2166/nh.2018.006
|View full text |Cite|
|
Sign up to set email alerts
|

Spatiotemporal impacts of land use land cover changes on hydrology from the mechanism perspective using SWAT model with time-varying parameters

Abstract: It is critically important to quantify the impact of land use land cover (LULC) changes on hydrology, and to understand the mechanism by which LULC changes affect the hydrological process in a river basin. To accurately simulate the hydrological process for a watershed like the Wei River Basin, where the surface characteristics are highly modified by human activities, we present an alternative approach of time-varying parameters in a hydrological model to reflect the changes in underlying land surfaces. The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 29 publications
1
44
0
1
Order By: Relevance
“…SWAT model has got the ability to simulate and predict the long-term changes of various hydrological elements under different land use types, soil types and management practices on the large scale complex basin (Abbaspour et al, 2007;da Silva et al, 2018;Gassman et al, 2007;Li et al, 2018;Liang et al, 2017). In SWAT model, runoff is firstly calculated for each Hydrological Response Unit (HRU) and then routed to obtain total runoff for the watershed.…”
Section: Swat Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…SWAT model has got the ability to simulate and predict the long-term changes of various hydrological elements under different land use types, soil types and management practices on the large scale complex basin (Abbaspour et al, 2007;da Silva et al, 2018;Gassman et al, 2007;Li et al, 2018;Liang et al, 2017). In SWAT model, runoff is firstly calculated for each Hydrological Response Unit (HRU) and then routed to obtain total runoff for the watershed.…”
Section: Swat Modelmentioning
confidence: 99%
“…Being important parts of environmental changes, the Land Use/Land Cover (LULC) change and climate change have significant impacts on the hydrological cycle through changing processes such as precipitation, evapotranspiration and infiltration, thus affecting the rainfall-runoff processes (Liu et al, 2008;Yin et al, 2017) and the amount of available water resources Luo et al, 2011). Therefore, the study of runoff response to LULC change and climate change is of great importance in water resources planning and management (Chen et al, 2018;Li et al, 2009Li et al, , 2018Liu et al, 2014;Pan et al, 2017;Yang et al, 2018;Yin et al, 2017;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1. The total drainage area of the watershed is 59 km 2 . Geographically, the area consists of lower Himalayas, sub-Himalayas, structural hills, terraces, flood plains, etc.…”
Section: Study Areamentioning
confidence: 99%
“…In the last two decades, many efforts were made to better understand the impacts of land use change on hydrological processes. The spatially distributed hydrological models were widely employed to predict the hydrological responses to land use change [1,2]. Conventionally, this is done by setting up a hydrological model for a baseline land use scenario (LUS).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrological models, including physical-distribution-based models, such as the European Hydrological System Model (MIKE-SHE), Topography Based Hydrological Model (TOPMODEL) [30], the Hydrologic Modelling System (HEC-HMS) [31,32], the Variable Infiltration Capacity (VIC) [33], the Soil and Water Assessment Tool (SWAT) [34], the Soil and Water Integrated Model (SWIM) [35], and the Water-Global Assessment and Prognosis (WaterGAP) [36], are capable of simulating temporal-spatial variations in hydrological processes and assisting us to understand the mechanisms of influence behind land use impacts [37][38][39][40][41][42]. Many studies have demonstrated the ability of SWAT to detect the impacts of land use and climate change on hydrological components in different areas [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%